Strategi Dakwah Islam dalam Pendekatan Rasional Transendental - Andy Dermawan (Al-Jami'ah Research Centre, 2002)
This article tries to apply the transcendental rational approach to the preaching of Islam. The characteristic preaching of Islam in transcendental rational approach relies on how ratio works in catching reality in the real world empirically, and then we analyze through an intergalactic combination between